The mediating effect of emotional schemas in the relationship between online gaming addiction and life satisfaction - Samet Makas; Mustafa Koç (Scientific Reports)
Abstract The present study examined the relationships between the levels of online game addiction among university students who play online games and their life satisfaction, emotional schemas, and demographic characteristics (gender and age). Additionally, structural equation modelling was conducted to examine the mediating effect of emotional schemas in the relationship between online gaming addiction and life satisfaction. The participants of the study consist of 549 university students who are enrolled in university and play online games. In the study, data were obtained using online gaming addiction scale, life satisfaction scale and leahy Emotional Schema Scale. The results of the study indicated a positive, low-level and statistically significant correlation between the level of online gaming addiction and the emotional schemas of weakness towards emotions, demand for rationality, difference, duration, validation, seeing emotions as harmful and guilt. Conversely, there were negative, low and statistically significant correlations with the emotional schemas of rumination, difference and duration. Furthermore, it was determined that emotional schemas exert a complete mediation effect on the relationship between online gaming addiction and life satisfaction.